2020
DOI: 10.1002/adfm.201909907
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring 2D Heteroatom‐Doped Carbon Nanosheets with Dominated Pseudocapacitive Behaviors Enabling Fast and High‐Performance Sodium Storage

Abstract: 2D carbon nanosheets are considered to be promising candidates for use as sodium ion battery (SIB) anodes due to their large specific surface area and excellent electronic conductivity. However, their applications are hampered by inferior cycling performance, insufficient storage capacity, and high cost. N, B co‐doping carbon nanosheets (NBTs) are synthesized using biomass‐based gelatin as carbon precursor and boric acid as template, and demonstrate their great potential as high‐performance SIB anodes in pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
72
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(74 citation statements)
references
References 58 publications
2
72
0
Order By: Relevance
“…[105,106] Recently, Jin et al reported the successful synthesis of N, B co-doping 2D carbon nanosheets (NBTs) using H 3 BO 3 as templates and low-cost gelatine as carbon precursors (Figure 13a). [31] The 2D nanosheet structure and heteroatom doping was shown to be beneficial to improve the electrode/electrolyte contact, created defects, and active sites for Na + adsorption and thus achieved improved storage capacity (309 mAh g −1 at 0.2 A g −1 for 200 cycles), excellent rate performance (192 mAh g −1 at 10 A g −1 ), and an already acceptable cyclability (225 mAh g −1 for 200 cycles at 1 A g −1 ). The sodium storage mechanism was also studied using ex situ X-ray diffraction (XRD) measurements at different states during first charge/discharge process.…”
Section: Heteroatom Dopingmentioning
confidence: 99%
See 2 more Smart Citations
“…[105,106] Recently, Jin et al reported the successful synthesis of N, B co-doping 2D carbon nanosheets (NBTs) using H 3 BO 3 as templates and low-cost gelatine as carbon precursors (Figure 13a). [31] The 2D nanosheet structure and heteroatom doping was shown to be beneficial to improve the electrode/electrolyte contact, created defects, and active sites for Na + adsorption and thus achieved improved storage capacity (309 mAh g −1 at 0.2 A g −1 for 200 cycles), excellent rate performance (192 mAh g −1 at 10 A g −1 ), and an already acceptable cyclability (225 mAh g −1 for 200 cycles at 1 A g −1 ). The sodium storage mechanism was also studied using ex situ X-ray diffraction (XRD) measurements at different states during first charge/discharge process.…”
Section: Heteroatom Dopingmentioning
confidence: 99%
“…[1][2][3][4][5] Rechargeable lithium-ion batteries (LIBs) as one of the state-of-the-art conductivity, and breaking graphitic packing. [30][31][32] The overall performance is, however, still not remarkable, and to achieve high capacity, stable cycling, and high Coulombic efficiency (CE) simultaneously from the first cycle is very difficult. Therefore, an in-depth understanding of the interaction processes toward the sodium storage in hard carbonbased anodes is highly profitable and in our opinion, the most promising way to resolve the current contradictious situation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To further improve Na-ion storage performance, another valid strategy is doping heteroatom to decorate the surface and structure of hard carbon, which can effectively enhance its electrical conductivity. [19][20][21][22][23][24] Among all the heteroatoms, sulfur doping in hard carbon could lead to an increase of lattice distance, which is in favor of the effective insertion and extraction of Na ion. Li et al 25 designed sulfur-doped disordered carbon by pyrolysis of precursor in sulfur steam, leading to excellent reversibility for Na-ion storage (271 mAh g -1 at 1 A g -1 after 1000 cycles).…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Secondly, carbon nanosheets have been explored as electrochemical active materials in the field of electrocatalysis due to their large surface area, superior mechanical/chemical stability and electronic properties. [28][29][30] Carbon sheets with edges have been studied as a model structure for hosting various ORR active sites. [31][32][33] The optimized twodimensional structure can provide excellent accessibility for reactants and products, thereby markedly enhancing mass transport efficiency.…”
Section: Introductionmentioning
confidence: 99%